2001
DOI: 10.1046/j.0953-816x.2001.01570.x
|View full text |Cite
|
Sign up to set email alerts
|

Deficient long‐term synaptic depression in the rostral cerebellum correlated with impaired motor learning in phospholipase C β4 mutant mice

Abstract: Long-term depression (LTD) at parallel fibre-Purkinje cell synapse of the cerebellum is thought to be a cellular substrate for motor learning. LTD requires activation of metabotropic glutamate receptor subtype 1 (mGluR1) and its downstream signalling pathways, which invariably involves phospholipase Cbetas (PLCbetas). PLCbetas consist of four isoforms (PLCbeta1-4) among which PLCbeta4 is the major isoform in most Purkinje cells in the rostral cerebellum (lobule 1 to the rostral half of lobule 6). We studied mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
75
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(80 citation statements)
references
References 55 publications
3
75
2
Order By: Relevance
“…1a). The localization and underlying mechanisms of eyeblink conditioning have been extensively studied by different approaches including gene targeting (6)(7)(8)(9)(10)(11), lesioning (12)(13)(14)(15), mutant analysis (16), and pharmacological inactivation analyses (17)(18)(19)(20)(21)(22)(23). On the basis of these studies, one model proposes an essential role of the cerebellar Purkinje cell circuit in memory traces (24)(25)(26).…”
mentioning
confidence: 99%
“…1a). The localization and underlying mechanisms of eyeblink conditioning have been extensively studied by different approaches including gene targeting (6)(7)(8)(9)(10)(11), lesioning (12)(13)(14)(15), mutant analysis (16), and pharmacological inactivation analyses (17)(18)(19)(20)(21)(22)(23). On the basis of these studies, one model proposes an essential role of the cerebellar Purkinje cell circuit in memory traces (24)(25)(26).…”
mentioning
confidence: 99%
“…It follows that impaired PF LTD should diminish motor learning, whereas more robust PF LTD would improve motor learning. Several mutant mice with diminished cerebellar LTD do display impaired motor learning (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%
“…Hirono et al (2001a) confirmed the observation by Miyata et al by analysing the other strain of PLCb4 knockout mice. Importantly, Miyata et al (2001) showed that delay eyeblink conditioning was severely impaired in the PLCb4 knockout mice. Since lobule simplex or lobule HVI of Larsell, a part of the cerebellar cortex with rich PLCb4 expression in the Purkinje cells, is crucial for delay eyeblink conditioning (Hesslow & Yeo 1998), these results indicate that PLCb4 is crucial for LTD and discrete motor learning in the rostral cerebellum.…”
Section: Long-term Depression (A) Discovery Of Ltdmentioning
confidence: 99%
“…Miyata et al (2001) analysed the PLCb4 knockout mice and found that both mGluR1-mediated Ca 2C mobilization and LTD were deficient in the rostral cerebellum, whereas these responses were intact in the caudal cerebellum. Hirono et al (2001a) confirmed the observation by Miyata et al by analysing the other strain of PLCb4 knockout mice.…”
Section: Long-term Depression (A) Discovery Of Ltdmentioning
confidence: 99%